Keragaman Genetik Kukang Jawa (Nycticebus javanicus) Menggunakan Control Region (D-loop) DNA Mitokondria (mtDNA) (GENETIC DIVERSITY ON JAVAN SLOW LORIS (NYCTICEBUS JAVANICUS) USING OF CONTROL REGION (D-LOOP) mtDNA) - Wirdateti, Wirdateti; Aziza, Hayati; Handayani, Handayani (Jurnal Veteriner, 2019)
Javan slow loris (Nycticebus javanicus)  one of the species of the genus Nycticebus is endemic in Java.  Their distribution region  is in West Java and Banten, and also reported to be found in Central Java and East Java, although very rarely.  Status of the species is Critically Endangered due to high levels of poaching, habitat loss and habitat fragmentation, so that the necessary conservation in order to increase the population. For conservation management it is necessary to know the status of genetic resources that play of  role in breeding, then this research is to explore the genetic population of the Javan slow loris  from some locations in West Java. The research objective was to assess the diversity of their current population of Java loris through the control region (D-loop) of mitochondrial DNA (mtDNA). A total of 23 individuals samples from Gunung Halimun Park, Tasikmalaya, Garut, Ciamis, Jember and confiscated at the Rehabilitation Center IAR Bogor were used in this stydy. Specific primers of D-loop are used for loris with a length of 296 bp sequence. The result showed there are only five different sites and formed six haplotypes, each haplotypes only 1-3 nucleotides different. Low genetic diversity is shown as much as 42.96% of individuals show the same sequence or genetic distance (d) = 0 that indicate was monomorf population from different population. The genetic distance of the entire population was 0.003 ± 0:01 (0.3%).